Tuḥfat al-fatā fī tafsīr sūrat Hal atā - Dashtakī, Ghiyāth al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
One of the challenges that the Qurʾān poses to its readers is the apparent contradictions that it contains. In order for these contradictions to be removed, Muslim scholars developed a doctrine according to which one verse could be abrogated by another. Abrogation being linked to temporality, the question whether a verse was revealed in Mecca or Medina became a major point of discussion. Ghiyāth al-Dīn Dashtakī (d. 949/1542) was one of the major representatives of the School of Shiraz in philosophy and a specialist in Peripatetic and Illuminationist philosophy, as well as mysticism. The present volume contains a new edition of his commentary on Sūrat al-Insān (no. 76), which is one of the suras on whose time of revelation much had already been written. In this seminal and innovative work, emphasis is given to a mystico-philosophical reading of the text, an appoach that would reach its zenith in the work of Mullā Ṣadrā (d. 1050/1640)